Intrinsic host range of the root-knot nematode Meloidogyne enterolobii and virulent M. incognita populations - Konigopal, Hemanth; Finckh, Maria R.; Bailly-Bechet, Marc; Danchin, Etienne G.J.; Kiewnick, Sebastian (Frontiers in Plant Science, 2025)
The root-knot nematode Meloidogyne enterolobii poses a significant challenge in agricultural production systems due to its damage potential and the ability to overcome plant resistance genes, which are effective against other root-knot nematode species. With little plant resistance available, few nematicides still allowed, crop rotation with non- or poor host plants is the only option for managing M. enterolobii. As virulence and pathogenicity can vary between Meloidogyne populations, determination of the intrinsic host range and pathogenicity of M. enterolobii populations is crucial for the implementation of effective management strategies in the future. In greenhouse experiments, the host range and pathogenicity of seven M. enterolobii populations were tested on 19 plant species. In addition, two populations of M. incognita, virulent against tomato Mi-1resistance gene, were included in this study, as they had demonstrated a similar range of reproductive potential and damage compared to M. enterolobii. The study revealed that tomato, eggplant, pepper, tobacco, cucumber, potato, bean, melon, sugar beet, yellow mustard, and soybean were good hosts for all tested Meloidogyne populations. However, variations in reproduction among populations were observed in carrot, cotton, phacelia, fodder radish, maize, sunflower, and peanut. In rose, none of the M. enterolobii populations reproduced (reproduction factor: RF< 0.1). However, virulent M. incognita populations allowed some multiplication with RF > 0.1, but below 1.0. Curiously, three M. enterolobii populations (M.ent3, 4 and5) showed a lower RF compared to the remaining populations, but were more damaging, resulting in reduced root and shoot fresh weight of the majority of the host plants tested. This is the first study comparing multiple populations of M. enterolobii, including the two type populations, from different geographic regions with a large panel of plant species. This study provides crucial information to develop new and sustainable control strategies against the quarantine nematode M. enterolobii.